Pengembangan Kurikulum Sekolah Dasar - Mubarak, Ruma (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
Education is an effort to prepare students to be able live well in the society, able to develop and improve the quality of their own lives, and contribute signifiantly in developing and improving the quality of society and nation . There are six main problems in the national education system, (1) decline moral and character of students, (2) equitable distribution oflearning opportunities, (3) low internal effiiency of the education system, (4) institutional status, (5) management of education that is not in line with the national development, (6) resources are not professional. In this case, need for social change which gives the direction that education is abasic approach in the change process. Education is life, therefore learning activities should be able to equip students with life skills (life competency) that appropriate with the environment and their lives.Keywords: Curriculum Development , Elementary School